2016
DOI: 10.21276/ijmrp.2016.2.5.023
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Haematological Parameters among Petrol Pump Workers in Bhubaneswar

Abstract: Background and objectives: Petrochemical workers are exposed to many noxious substances present in their work places. The most dangerous effects are due to benzene which is mostly found in petrochemical vapors. It is a well known carcinogen with relative hematotoxicity. So in our study we have assessed the hematological parameters (i.e. absolute eosinophil count, hemoglobin concentration, platelet count) of petrol pump workers in and around Bhubaneswar. Methods: This study was conducted in the department of Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(14 reference statements)
0
0
1
Order By: Relevance
“…Similar to our findings, the study in Bhubaneswar found no statistically significant difference in platelet count between the gasoline exposed and control group. 27 In contrast to current findings, UK study from Texas City found that participants exposed to benzene had a non-significantly higher platelet count. 16 , 20 According to the current study, gasoline station worker had a higher WBC count than the control groups, but it is not statistically significant.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to our findings, the study in Bhubaneswar found no statistically significant difference in platelet count between the gasoline exposed and control group. 27 In contrast to current findings, UK study from Texas City found that participants exposed to benzene had a non-significantly higher platelet count. 16 , 20 According to the current study, gasoline station worker had a higher WBC count than the control groups, but it is not statistically significant.…”
Section: Discussioncontrasting
confidence: 99%